Reorienting information searching research by applying a situated abilities perspective - Berget, Gerd (Information Research an international electronic journal, 2024)
Introduction. In studies of information searching, people are often characterised with perpetual physical, sensory and cognitive abilities. Situational factors that may affect human abilities are less considered, although they may have an impact on information searching behaviour. For example, a person with dyslexia may struggle with inputting correctly spelled queries. Spelling skills, however, may also be influenced by fatigue, illness, or using a mobile phone while walking. All types of users can therefore at certain times experience challenges related to query input. Method. This theoretical paper explores the concept of situated abilities in the context of information searching. Eight personas are constructed and used in a discussion of how a change of perspective on human abilities can provide a valuable contribution to research. Analysis. The personas are based upon empirical findings of user behaviour and are discussed in relation to theoretical frameworks and models. Results. Human abilities are dynamic and affected by a variety of situational factors. All people experience temporary impairments during their lives. It would therefore be purposeful to reorient information searching research by applying a situated abilities perspective. Conclusion. A situated abilities perspective may result in more inclusive search systems for all types of users.